Ответ:
Объяснение:
121.
(a/3+b/6)* 1/2a+b)= (6a+3b)/18 * 1/(2a+b)=3(2a+b)/18 *1/(2a+b)=3/18=1/6
123.
(x/y-y/x)*2xy/(x-y)=(x²-y²)/xy * 2xy/(x-y)=(x-y)(x+y) *2/(x-y)=2(x+y)
125.
(5+a/b) *b/(5b+a)²=(5b+a)/b*b/(5b+a)²= 1/(5b+a)
127.
(a-3)/(a+3) *[ (a+a²/(3-a)]=(a-3)/(a+3) *[a(3-a)+a²]/(3-a)= =-(3-a)(a+3)* (3a-a²+a²)/(3-a)=
= -3a/(a+3)
129.
(x+5)/(x³+25x) * [(x+5)/(x-5) +(x-5)/(x+5)=(x+5)/x(x²+25) *[(x+5)²+(x-5)²]/(x²-25)=
=(x+5)/x(x²+25) *[(x²+10x+25+x²-10x+25)/(x-5)(x+5)]=(x+5)/x(x²+25) *(2x²+50)/(x-5)(x+5)=1/x(x²+25) *2(x²+25)/(x-5)= 1/x(x-5)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
121.
(a/3+b/6)* 1/2a+b)= (6a+3b)/18 * 1/(2a+b)=3(2a+b)/18 *1/(2a+b)=3/18=1/6
123.
(x/y-y/x)*2xy/(x-y)=(x²-y²)/xy * 2xy/(x-y)=(x-y)(x+y) *2/(x-y)=2(x+y)
125.
(5+a/b) *b/(5b+a)²=(5b+a)/b*b/(5b+a)²= 1/(5b+a)
127.
(a-3)/(a+3) *[ (a+a²/(3-a)]=(a-3)/(a+3) *[a(3-a)+a²]/(3-a)= =-(3-a)(a+3)* (3a-a²+a²)/(3-a)=
= -3a/(a+3)
129.
(x+5)/(x³+25x) * [(x+5)/(x-5) +(x-5)/(x+5)=(x+5)/x(x²+25) *[(x+5)²+(x-5)²]/(x²-25)=
=(x+5)/x(x²+25) *[(x²+10x+25+x²-10x+25)/(x-5)(x+5)]=(x+5)/x(x²+25) *(2x²+50)/(x-5)(x+5)=1/x(x²+25) *2(x²+25)/(x-5)= 1/x(x-5)